Doris Howes Calloway: Her Work and Legacy on Nutritionally Vulnerable Populations in North America. Issue 6 (November 2022) - Butte, Nancy F.; Kuhnlein, Harriet V.; Murphy, Suzanne P.; Yates, Allison A.; King, Janet C.; Kretsch, Molly J.; Blackburn, Mary L.
Abstract : Dr Doris Howes Calloway had a keen interest in nutritionally vulnerable populations in North America and around the world. Given her scientific reputation and interests, she advised many national and international agencies on improving the health and well-being of populations at increased risk of malnutrition. In North America, she and her graduate students laid the groundwork for improvement of the diets of several Indigenous peoples including the Cocopah, Hopi, and Navajo. They found that improvement of the nutritional and health status of the Cocopah tribe was unlikely without addressing underlying social and economic factors. Among the Hopi tribe, the replacement of traditional foods by energy-dense foods of low nutritional quality increased the risks of nutrient inadequacies and obesity. Dr Calloway also had a keen interest in understanding the effects of nutrition on biological functions that increase nutritional demand and thus vulnerability, as demonstrated in studies of pregnancy and lactation among Navajo women, and growth of children from Mexican American farmworker families. They demonstrated the limits of federal nutrition programs at that time. They identified the double burden of stunting and obesity among Mexican American children. Dr Calloway's standards of academic excellence and rigorous research influenced her students to pursue careers that enhanced science-based policies and programs to promote the health and wellness of nutritionally vulnerable populations.